Effect of exfoliated graphene defects on thermal conductivity of water based graphene nanofluids - Rahat, Arifutzzaman; Ismail, Ahmad Faris; Yaacob, Iskandar Idris; Khan, Ahsan Ali; Mohammad, Zahangir Alam (Research India Publications, 2018)
In this work, sonication assisted exfoliated Graphene (Gr) was separated into five different suspensions using a systematic centrifugation scheme (4000-500 rpm) for the two different solvents N-Methyl-2-Pyrrolidone (NMP) and N, Ndimethylformamide (DMF). Gr dispersions in deionized water (DW) were prepared by the re-dispersion process with the aid of vacuum filtration. Systematic thermal conductivity (TC) measurements were conducted separately on the prepared Gr dispersion in DW with rising temperature ranging from 25 to 60 oC. Defects in exfoliated Gr samples were identified in terms of intensity ratio of D and G band (ID/IG) of Raman spectroscopy. For a fixed time of sonication values of ID/IG were found considerably higher in higher centrifugation speed (rpm). This phenomenon was perceived for both of the solvents. However, obtained values of ID/IG for the exfoliated Gr in NMP (Gr-NMP) were lower than that of Gr exfoliated by DMF (Gr-DMF). Lowest values of ID/IG found for 500 rpm, were 0.697 and 0.879 for the Gr-NMP and Gr-DMF respectively. Effect of exfoliated Gr defects were evaluated on the TC of Gr dispersed DW nanofluids. At 60 ℃, TC of GrNMP dispersion in DW was obtained 1.146 W/m-K for ID/IG of 0.697 (500 rpm) and 0.935 W/m-K for ID/IG of 0.916 (4000 rpm). Similarly occurrence was also apparent for the Gr-DMF dispersion in DW.